Grammar and Its Teaching: Representations of Language Pedagogy Students - Rubio-Manriquez, M; Moya-Munoz, P (UNIV BUENOS AIRES, INST LINGUISTICA, 2024)
The aim of this research focuses on describing the representations about grammar and its teaching expressed in their discourse by Language Pedagogy students from four universities from the Metropolitan Region of Chile. The methodology adopted is a multiple case study with a qualitative approach. For this purpose, group interviews were conducted with students from four different universities who were in their third and fourth year of their degree. The interview was guided by a semi-structured guideline and the analysis strategy was inductive. Thematic segmentation was carried out in order to identify the associated sub-themes. Then, the characterization by sub-theme was carried out to finally relate and validate the categories that emerged. The results indicate that the teaching of grammar is understood as a disciplinary area that is not associated with the explicit development of skills, which is related to the fact that in the university context it is perceived as a complex discipline whose appropriation requires effort that is experienced, by some students, as an interesting challenge and, by others, as something overwhelming because it involves effort, order and exercise. In any case, they recognize that they have not been taught how to teach grammar, which means that they tend to repeat the model implemented by the teacher when it is evaluated as positive.